Perancangan Ulang Museum Tekstil Jakarta Dengan Pendekatan Teknologi - Hanifah, Nadhimatul; Cardiah, Tita; Murdowo, Djoko (Telkom University, 2024)
This design project re-examines the interior of the Jakarta Textile Museum to address